Compliance for community-based cervical cancer screening program among women of age 30-65 years residing in low socioeconomic settings of Mumbai, India - Vasundhara Yalguresh Kulkarni; Gauravi Ashish Mishra; Sharmila Anil Pimple; Heena Kauser Aslam Shaikh; Aanchal A Awasthi (Wolters Kluwer Medknow Publications, 2022)
Background: Low participation in screening and poor follow-up are major challenges in implementing population based screening in developing countries. Determinants of participation in a community-based organized cervical cancer screening program are discussed here. Objectives: The objectives were to study factors determining compliance of women for cervical cancer screening in an urban low socioeconomic setting. Methodology: Community-based service program was conducted for screening uterine cervix cancers with a visual inspection of the cervix on the application of 5% acetic acid by trained primary health workers. The process involved the selection of clusters, household surveys, health education, and screening of eligible women for uterine cervix cancer. Logistic regression analysis was conducted to identify determinants of participation in cervical cancer screening. Results: A total of 138,383 population were surveyed, of which 21,422 eligible women were contacted and 16,424 (82.50%) complied for screening. According to the results of univariate and multivariate analysis, women belonging to the age group of 30-39 (80.69%), literate women with school level or education up to Senior College (78.97% and 80.86%) (odds ratio [OR], 1.323; P ≤ 0.001) and (OR, 1.402; P ≤ 0.001), belonging to Hindu religion (77.20%), speaking Marathi (77.07%), and with a family history of cancer (81.93%) had higher participation for screening, while women belonging to the Muslim community (73.95%) (OR, 0.743; P ≤ 0.001), speaking other than Marathi and Hindi language (73%) (OR, 0.872; P = 0.017), illiterate women (70.71%), and graduate women (70.78%) had lower participation. Conclusion: High compliance can be achieved by providing good-quality health education and setting up of screening clinics in vicinity of participating women.